Effect of plasma chemical oxidation of ethylene impurities on the efficiency of kiwifruit storage - Yegorov, M.O.; Taran, G.V.; Zamuriev, O.O.; Opalev, P.O. (Problems of Atomic Science and Technology, 2023)
The effectiveness of plasma chemical technology in reducing the concentration of ethylene impurities in order to extend the shelf life of kiwifruit has been studied. Ethylene and mold were controlled by plasma treatment, which slowed the ripening of kiwifruit and significantly inhibited rotting. When storing kiwifruit using the plasma chemical system, the level of ethylene was twice lower than that measured in the control batch. Also, the level of ethylene practically did not change during the entire period of the experiment, since the ethylene released from the fruit was quickly oxidized by ozone. Air treatment of kiwifruit storage environment resulted in the fact that ripening mechanism was delayed and the loss of fruits during their further transportation and storage was almost completely prevented. Thus, high efficiency of plasma-chemical method for extending kiwifruit shelf life was shown as well as the prospects of its application. Storage period can be doubled while preserving the subtle aroma of fruits. The effectiveness of plasma chemical technology in reducing the concentration of ethylene impurities in order to extend the shelf life of kiwifruit has been studied. High efficiency of plasma-chemical method for extending kiwifruit shelf life was shown as well as the prospects of its application. Storage period can be doubled while preserving the subtle aroma of fruits.